(untitled) - White, Wayne A. (Boca Raton, FL, 2013)
Written for students, researchers, and academics involved in environmental and social sciences, as well as land owners and managers, this reference is the first of its kind to cover biosequestration for a broad audience. The author covers the scientific evidence of biosequestration, the various land practices that sequester carbon, and policies in place to encourage such practices. It includes examples of actions taken by the author that can be used by gardeners, farmers, ranchers, and those in land management. It also focuses on several issues of importance: global warming, carbon pollution, sustainable agriculture, ecological problems of conventional agriculture, and land management
Keywords: Carbon sequestration,Climatic changes,Hấp thụ carbon,Biến đổi khí hậu; Environmental aspects,Khía cạnh môi trường